ANALISIS KANDUNGAN VITAMIN C DAN DAYA TERIMA ORGANOLEPTIK YOGHURT SARI BUAH NAGA MERAH (Hylocereus sp) - Chairunnisaa Chairunnisaa; Anang Wahyudi; Yenni Okfrianti (JURNAL PENELITIAN TERAPAN KESEHATAN, 2020)
Abstract: The higher the Red Dragon fruit juice is added then the content of vitamin C fruit yogurt will increase. This is due to the content of vitamin C on the red Dragon fruit in the fruit yogurt is not too much decreased because of the stable nature of vitamin C in acidic State. The purpose of this research is to know the analysis of vitamin C content and the receipt of organoleptic yogurt juice red dragon fruit. This research uses the complete random draft (RAL) factorial method with 2 factors. Factor I is vitamin C level. The factor II is the concentration of red dragon fruit juice (10%, 15%, 20%).Results of the highest vitamin C levels in yogurt in the dragon fruit juice yogurt with a concentration of A4 (20%) With a rate of vitamin C as much as 1, 584mg/100gram. There is a significant range of organoleptic power of gratitude for the taste of the 4 red Dragon Juice Yogurt treatment (0%, 10%, 15%, and 20%). There is no difference in the level of color, aroma, and viscosity of red dragon juice yogurt. The favorite level of color in red dragon fruit yogurt is in the treatment of A2 (10%) and A4 (20%). The favorite level of flavor in red dragon juice yogurt is on the A4 (20%) treatment. The favorite level of aroma in red dragon juice yogurt is found in A4 (20%) treatment. The favorite level of color in red dragon juice yogurt is in the A3 (15%) treatment. It is suggested in subsequent studies to identify total lactic acid bacteria in the red dragon juice yogurt. Further product development of yogurt concentration type is most liked.Keywords: Vitamin C content, organoleptic receiving power, dragon fruit juice yogurt.